#### Answer

Refer to the image below for the graph.

#### Work Step by Step

Write the given equation in the form $y=mx + b$ to obtain:
$-y = -3x+4
\\-1(-y) =-1(-3x+4)
\\y = 3x-4$
(note that this equation is equivalent to the original equation)
To graph this equation, perform the following steps:
(1)
Create a table of values by assigning $x= -6, -3, 0, 3, 6$ and then solving for the corresponding value of $y$ for each one.
(refer to the attached image below)
(2)
Plot each point from the table of values; then, connect them using a line.
(refer to the attached image in the answer part above)